Differential Proliferation and Maturation of Subcortical Astrocytes During Postnatal Development - Shoneye, Temitope; Orrego, Alessandra Tamashiro; Jarvis, Rachel; Men, Yuqin; Chiang, Ming Sum R.; Yang, Yongjie (Frontiers in Neuroscience, 2020)
Astrocytes exhibit a clear region-dependent molecular and functional heterogeneity in the CNS. Although cortical astrocytes proliferate robustly within the first two postnatal weeks, the temporal proliferation dynamic of astrocytes in subcortical regions during postnatal development remains essentially unknown. Whether subcortical astrocytes mature similarly as cortical astrocytes is also unexplored. By employing genetic labeling of astrocytes and pulse-chase EDU labeling of proliferating cells, we found that astrocytes tend to proliferate at a lower rate in the hypothalamus within the first two-week period but increase their proliferation rate in weeks 3-4 when cortical astrocytes have nearly completed proliferation. We also found that astrocytes in representative subcortical regions have a modest growth of their domain size and exhibit a significantly smaller domain size compared to cortical astrocytes at P30 when astrocytes generally complete postnatal maturation. In addition, we generated and characterized eaat2-iCreERT transgenic mice in which the improved and inducible Cre (iCreERT) is driven by the large human eaat2 promoter (8.3kb) for astrocyte gene targeting. We found that eaat2-iCreERT mice are able to efficiently (>80%) and specifically (~80% except frontal cortex) target cortical astrocytes using Ai14-tdT reporter mice. However, their targeting efficiency (~50%) and specificity (~60%) in subcortical (thalamus and hypothalamus) astrocytes is inadequate. In summary, our study unveiled how subcortical astrocytes undergo postnatal proliferation and maturation. Our newly generated eaat2-iCreERT mice can serve as an alternative and important tool for gene targeting in (cortical) astrocytes.